Membuat Card Game Edukatif Yang Menyesuaikan Keinginan Konsumen - Elissa Ambarwati; Paulina Tjandrawibawa (Jurnal Vicidi, 2018)
Board game and Card game now quite popular, but there’s still some game that can not suit for consumer needs of educative game. This research aims to find out about how to make a educative game dan that consumer liked. For that needs some interview with expert and extreme user that understand about Surabaya culture and Game master. From this research, found out that to make a educative card game, there are a view elements that need to understand before planning on making game is to research the target consumer, Genre game, Game play, also create interfaces that will not bothering the player.